2020
DOI: 10.1038/s41379-019-0367-9
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability in upfront dichotomous histopathological assessment of ductal carcinoma in situ of the breast: the DCISion study

Abstract: Histopathological assessment of ductal carcinoma in situ (DCIS), a non-obligate precursor of invasive breast cancer, is characterized by considerable inter-observer variability. Previously, post hoc dichotomization of multi-categorical variables was used to determine the 'ideal' cut-offs for dichotomous assessment. The present international multi-center study evaluated inter-observer variability among 39 pathologists who performed upfront dichotomous evaluation of 149 consecutive DCIS.All pathologists independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…21 An alternative two-tier grading system (high vs non-high grade) has been proposed; 22 however, one recent international study of 149 DCIS cases assessed by 39 breast pathologists using such a dichotomous grading system still showed only moderate agreement (kappa = 0.422). 23 As several worldwide trials are presently being undertaken of active surveillance vs surgical intervention for low-risk DCIS, 12 including the LORIS, 9 LORD 10 and the COMET trials 11 , the reproducible grading of DCIS is increasingly important for clinical management and methods for improving reproducibility require further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…21 An alternative two-tier grading system (high vs non-high grade) has been proposed; 22 however, one recent international study of 149 DCIS cases assessed by 39 breast pathologists using such a dichotomous grading system still showed only moderate agreement (kappa = 0.422). 23 As several worldwide trials are presently being undertaken of active surveillance vs surgical intervention for low-risk DCIS, 12 including the LORIS, 9 LORD 10 and the COMET trials 11 , the reproducible grading of DCIS is increasingly important for clinical management and methods for improving reproducibility require further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore firstly would suggest to objectify histological grading by using a numerical semi-quantitative scoring system which separately evaluates each of these features, analogous to the modified Bloom and Richardson grading system for IBC [ 42 , 43 ]. Dichotomous scoring systems may further improve reliability and prognostic value and should be further explored evaluating different cut-offs [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in comparison to grading of invasive breast cancer, which is performed according to the modified Bloom and Richardson grading classification (Elston-Ellis modification) [33,34], with scoring of the three subcategories (tubular differentiation, nuclear polymorphism and mitotic count) grading of DCIS is less standardized. Recently, dichotomous histopathological assessment of ductal carcinoma was studied as an alternative with (better) acceptable degrees of interobserver variability, however, interobserver variation remained considerable and at best acceptable [35]. In addition, other recent data showed that even among 35 expert breast pathologists, the threshold for comedonecrosis is highly variable [36].…”
Section: Discussionmentioning
confidence: 99%